Knowledge translation approaches and practices in Indigenous health research: A systematic review. (May 2022) - Morton Ninomiya, Melody E.; Maddox, Raglan; Brascoupé, Simon; Robinson, Nicole; Atkinson, Donna; Firestone, Michelle; Ziegler, Carolyn; Smylie, Janet
Abstract: Knowledge translation (KT) is a critical component of any applied health research. Indigenous Peoples' health research and KT largely continues to be taught, developed, designed, regulated, and conducted in ways that do not prioritize local Indigenous Peoples' ways of sharing knowledges. This review was governed and informed by Indigenous health scholars, Knowledge Guardians, and Elders. Our systematic review focused on answering, what are the promising and wise practices for KT in the Indigenous health research field ? Fifty-one documents were included after screening published literature from any country and grey literature from what is now known as Canada. This included contacting 73 government agencies at the federal, territorial, and provincial levels that may have funded Indigenous health research. Only studies that: a) focused on Indigenous Peoples' health and wellness; b) documented knowledge sharing activities and rationale; c) evaluated the knowledge sharing processes or outcomes; and d) printed in English were included and appraised using the Well Living House quality appraisal tool. The analysis was completed using an iterative and narrative synthesis approach. Our systematic review protocol has been published elsewhere. We highlight and summarize the varied aims of Indigenous health research KT, types of KT methodologies and methods used, effectiveness of KT efforts, impacts of KT on Indigenous Peoples' health and wellness, as well as recommendations and lessons learned. Few authors reported using rigorous KT evaluation or disclosed their identity and relationship with the Indigenous communities involved in research (i.e. self-locate). The findings from this review accentuate, reiterate and reinforce that KT is inherent in Indigenous health research processes and content, as a form of knowing and doing. Indigenous health research must include inherent KT processes, if the research is by, for, and/or with Indigenous Peoples. Highlights: Effective KT is directed, governed, &/or led by Indigenous rightsholders. KT must reflect contextually relevant principles, practices, language, & protocols. KT is rarely evaluated using Indigenous-led, clear, or rigorous methodologies. Our review involved Indigenous scholars, Elders, & trainees throughout. KT processes are as critical as the content.